2009
DOI: 10.1093/annonc/mdn551
|View full text |Cite
|
Sign up to set email alerts
|

Effective second-line chemotherapy for extranodal NK/T-cell lymphoma consisting of etoposide, ifosfamide, methotrexate, and prednisolone

Abstract: This chemotherapy regimen was moderately effective for relapsed/refractory extranodal NTCL, nasal type. Toxic effects were moderate, but caution should be exercised to prevent severe infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…11 The complete response rate to conventional chemotherapy in patients with stage III or IV disease is less than 15%, 24,25 whereas 6 of our 7 patients with stage IV disease responded, with 4 of them entering complete remission (50%). These results, obtained in a prospective trial, confirm those obtained by the Chinese group who first reported the use of asparaginase to treat NK/T-cell lymphoma, in 4 retrospective series.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…11 The complete response rate to conventional chemotherapy in patients with stage III or IV disease is less than 15%, 24,25 whereas 6 of our 7 patients with stage IV disease responded, with 4 of them entering complete remission (50%). These results, obtained in a prospective trial, confirm those obtained by the Chinese group who first reported the use of asparaginase to treat NK/T-cell lymphoma, in 4 retrospective series.…”
Section: Discussionmentioning
confidence: 71%
“…Chemotherapy protocols used for lymphomas of other histologic subtypes are poorly effective, at least in part, because of frequent multidrug resistance gene expression by tumor cells. 9 Patients with disseminated or relapsing disease have a very poor outcome, 4,10,11 and there is no standard management for relapsed or refractory disease. We and others, in small retrospective studies, [12][13][14][15][16] have observed very good response and survival rates in patients treated with L-asparaginase, a drug with an original antitumoral mechanism not affected by MDR.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the results of a single-institution but well-designed prospective phase II study were published [53]. In this study, 32 patients with relapsed or refractory ENKL were treated with IMVP-16/Pd (ifosfamide, methotrexate, etoposide, and prednisolone) therapy as a secondline chemotherapy from October 1996 to February 2002.…”
Section: Clinical Trials In the Early 2000smentioning
confidence: 99%
“…Chemotherapy may yield more benefits by reducing the risk of distant metastasis. However, anthracycline-based chemotherapy regimens (e.g., cyclophosphamide, doxorubicin, vincristine, and prednisone [CHOP]) have shown disappointing efficacy for NKTCL, partially due to the overexpression of a multidrug-resistant gene in NKTCL cells [7][8][9]. Novel regimens containing Lasparaginase (L-ASP) or pegaspargase have elicited promising responses [10][11][12].…”
Section: Introductionmentioning
confidence: 99%